Intragenotypic variability of Capsicum chinense Jacq. “ají Supano” from the lower river basin of the Supe- Barranca - Aliaga Camarena, Juana (2019)
Capsicum chinense “ají supano” is an ecotype typical of the countryside of Supe veryappreciated in the regional cuisine for its aroma and flavor. This ecotype to date hasno studies, so the objective of the present study is to characterize it molecularly toidentify intragenotypic variability of 30 individuals of chili peppers from the lowerSupe river basin using molecular markers ISSR. Fruits were collected from fourfarmers during the month of November, 2016, being the seeds selected randomly,for their establishment in pots in house mesh. DNA was extracted from three youngleaves using the Micro - CTAB method modified by Biotechnology Lab of PIPS inCereals and Native Crops of UNALM to molecular analysis. Primers SSR 22, UCB807, UCB 810 and UCB 841 were selected due their high resolution and banding;which did not detect different bands among the individuals evaluated, confirming thatit is an autogamous ecotype, all the individuals of the population are genetically equal,therefore there is no intragenotypic variability